Tracing (Dis)Continuities: Education Reforms in Socialist Yugoslavia and its Successor States (KULT_online, 2015)
Contrary to what the title might suggest, this volume offers a compelling analysis of the correlation between educational policies and the wider socio-political context they stem from and partially shape. By examining three ˈcritical juncturesˈ from the (recent) past, i.e. the vocation-oriented education reform in socialist Yugoslavia, the introduction of religious and civic education in post-Milošević Serbia, and the establishment of ˈethnicˈ universities in post-conflict Sandžak, Kosovo, and Macedonia, Bacevic argues that some educational policies reproduced or even exacerbated existing divisions. This contributed to the creation of certain subjectivities and group identities.